MATURITY LEVEL DAN MANAGEMENT AWARENESS PADA PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI PERUSAHAAN TUNAS KREASI MANDIRI - Suryani, Nining (LPPM Universitas Nusa Mandiri, 2013)
Currently, almost all areas of life utilizing information technology, many companies that provide IT services example IT consulting company. But whether these companies had been optimally utilized existing technology to the company itself, so there is alignment between business objectives and utilization of existing IT in general and whether the company engaged IT has met the standard IT governance, one of which is COBIT framework 4.1, especially in data processing. Questionnaires and interviews conducted to determine whether specific IT governance data management processes that take place now still have weaknesses, and how the strategy of corrective measures in the existing data management processes in technology consulting company. A weakness that occurs is the lack of defining a detailed mechanism for describing the data flow that occurs, there are no formal procedures and requirements for data storage and security of data is done by each unit accordance with the needs of those units, because there are no formal procedures in conducting the company's data security. To step improvements in data management processes by formulating the necessary policies and procedures on data management processes, using tools to automate the process of data and provide training to employees on a regular basis.